The impact of dominant logic and competitive intensity on SMEs performance: A case from China - Kashif Ullah Khan; Zhang Xuehe; Fouzia Atlas; Farhan Khan (Journal of Innovation & Knowledge (JIK), 2019)
Intangible resources are widely considered the main source of gaining competitive advantage and sustain superior performance in transition and emerging economies such as China, particularly in SMEs sector. In this paper, we argue theoretically (under resource-based view RBV) and demonstrate empirically that intangible resources (e.g. dynamic managerial capabilities (DMC) and dominant logic (DL)) are indispensable for long-term superior firm performance. We calculate CFA to test the measurement model. With an empirical study of 328 SMEs in China, the results indicate that highly competitive environment facilitates the impact of dominant logic on firm performance. Furthermore, our results also support that there is a significant mediating role of dominant logic between dynamic managerial capabilities and firm performance. In the end, we discussed managerial implications and theoretical contributions.
Keywords: 650; SMEs; Dominant logic; Dynamic managerial capabilities; Performance and competitive intensity